Thinking outside the Box The Case of the Sun-God Tablet and the Cruciform Monument - Finkel, Irving L. 1951-; Fletcher, Alexandra (2016)
The stimulus for this article has been the reworking of displays within the Raymond and Beverly Sackler Wing at the British Museum. The need for a cohesive narrative led us to look hard at objects that have reposed in the museum's collections since the 19th century and, in particular, to "reopen" the case of the Sun-God Tablet and the Cruciform Monument. It turned out that most of the long-cherished assumptions about these objects failed to withstand modern scrutiny. With the benefit of Hormuzd Rassam's original papers, we have now been able to reconsider the finds as a whole, with surprising consequences.
Keywords: British Museum; COLLECTION management (Museums); Cruciform Monument; Ebabbar (Sun-God Temple); History; Hormuzd Rassam; MUSEUM techniques; Nabonidus; Nabu-apla-iddina; RASSAM, Hormuzd; Sippar (Extinct city); Sippar; Sun-God Tablet; museology; pious fraud